Dolphins and Boats: When Is a Disturbance, Disturbing? - New, Leslie; Lusseau, David; Harcourt, Robert (Frontiers in Marine Science, 2020)
Globally, exploitation of marine mammals has shifted from hunting to viewing over the last few decades. While refraining from actively killing animals may have a positive effect on marine mammal populations, whale and dolphin watching can induce changes such as displacement from preferred habitat and disruption of foraging that may also have severe fitness costs. Under some circumstances, this non-lethal disturbance may affect populations in a manner similar to directed mortality. Here, we focus on inshore dolphin populations that are known to show short-term behavioural responses to boat approaches. Long-term fitness effects have only been clearly identified in a small number of these populations, and all share certain characteristics, i.e. closed, small and food limited. This raises the question of importance of context when considering the long-term effects of disturbance, since many dolphin populations may be open, large, and/or free from resource restriction. We explored the effect of disturbance based on the characteristics of populations using the population consequences of disturbance (PCoD) framework. PCoD was developed to link short-term changes in individual behaviour and physiology to presumed long-term effects on population dynamics. To ensure our scenarios were biologically plausible, they reflected the ecological context of four well-studied populations of dolphins, Doubtful Sound NZ, Sarasota Bay USA, Durban Bay SA and Jervis Bay AUS, in terms of their size, closure and food resources. We found that the characteristics of the populations being disturbed are important with regards to the level of disturbance that could be tolerated. Closed populations were most sensitive, while large, open populations with no food limitation appeared to be able to withstand a higher probability of disturbance. This implies that population characteristics should be accounted for when determining the suitability of whale and dolphin watching operations in a given area.